Chaotic sequences based watermarking wireless physical layer security authentication algorithm - CHEN Songlin (Dianxin kexue)
In recent years, wireless mobile consumers have also grown exponentially. Due to the openness and broadcasting of the wireless networks, it is easier for unauthorized users to disguise themselves as legitimate users to launch spoofing attacks, resulting in insecurity in the low-altitude industry. Relying on specific cryptographic algorithms alone in the tradition was difficult to cope with password cracking abilities of high-intensity and high-computility. Meanwhile, a secure mechanism for covert communication was urgently needed. A chaotic sequences based watermarking wireless physical layer security authentication algorithm was proposed. This algorithm utilized the transmission of chaotic watermark and carrier information together to achieve covert transmission of service data, and physical layer identity authentication was completed without occupying additional frequency band resources of the system. Through analysis of simulation experiments, this method could embed watermark information by using different modulation methods, and the physical layer security authentication performance was significantly improved via adjusting the watermark power coefficient.